2023
DOI: 10.1002/adhm.202203087
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin‐Primed Mesenchymal Stem Cells‐Derived Small Extracellular Vesicles Alleviated Neurogenic Erectile Dysfunction by Reversing Phenotypic Modulation

Abstract: Erectile dysfunction (ED) is an adverse side effect of pelvic surgery with no effective treatment. In this study, it is explored whether melatonin could improve the therapeutic effects of small extracellular vesicles (sEVs), derived from mesenchymal stem cells (MSCs), on cavernous nerve injury (CNI) ED, and the underlying mechanisms are investigated. The sEVs from melatonin‐pretreated MSCs (MT‐EVs) and MSCs (NC‐EVs) are isolated and applied to CNI ED. Transplantation of MT‐EVs remarkably increases erectile fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This analysis was based on previous reports on the transduction of the PKIA/RhoA/ROCK signal in endothelial cells [ 88 , 89 ]. As a result, it was evident that Mel-EV could effectively suppress the phenotypic regulation of CSMC through the miR-10a-3p/PKIA/RhoA/ROCK axis, leading to significant improvement in cavernous nerve injury erectile dysfunction (CNI ED) [ 90 ]. Analysis of selenium, a known factor that influences MSC proliferation, multipotency, and anti-inflammatory effects, treated ADMSC-derived EV (Sel-EV), produced results like those of EV characteristics regulated by the previously mentioned substances.…”
Section: Engineering Methods Of Ev and Applications For Regenerative ...mentioning
confidence: 99%
“…This analysis was based on previous reports on the transduction of the PKIA/RhoA/ROCK signal in endothelial cells [ 88 , 89 ]. As a result, it was evident that Mel-EV could effectively suppress the phenotypic regulation of CSMC through the miR-10a-3p/PKIA/RhoA/ROCK axis, leading to significant improvement in cavernous nerve injury erectile dysfunction (CNI ED) [ 90 ]. Analysis of selenium, a known factor that influences MSC proliferation, multipotency, and anti-inflammatory effects, treated ADMSC-derived EV (Sel-EV), produced results like those of EV characteristics regulated by the previously mentioned substances.…”
Section: Engineering Methods Of Ev and Applications For Regenerative ...mentioning
confidence: 99%
“…Some extensively used modification techniques include click chemistry‐based strategies for EV surface labelling using fluorescent beads, quantum dots, and supermagnetic particles, as shown in Figure 2. Studies indicate that MSC‐EVs have shown substantial therapeutic potential in various disease conditions without any modification (Chen et al., 2023, Rani et al., 2015, Yang et al., 2023, Zeng et al., 2022). However, these EVs are often complemented with specific formulations, adhesives, or hydrogels to increase their intrinsic therapeutic efficiencies (Liu et al., 2023, Wang et al., 2023).…”
Section: Ev‐engineering and Drug‐loading Strategies For Ev‐mediated D...mentioning
confidence: 99%